(untitled) - Baker, Michael John (New York, 2007)
This is a review and analysis of the issues involved in managing products through their life cycle. The work has a managerial orientation and will be ideal for students of marketing, business studies and product development courses.
Keywords: Quản lý sản phẩm,Product management,New products; Management